2003
DOI: 10.21236/ada416512
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Model for Growth of the Submersed Aquatic Macrophyte Sago Pondweed (Potamogeton pectinatus L.)

Abstract: A simulation model for biomass dynamics of the submersed macrophyte Potamogeton pectinatus L. is presented. The model (POTAM) is based on carbon flow through the vegetation in meter-squared (m^) water columns. It includes descriptions of several factors that affect biomass dynamics, such as site characteristic changes in climate, temperature, water transparency, water level, pH, and oxygen effects on CO2 assimilation rate at light saturation, wintering strategies, mechanical control (removal of shoot biomass),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…Although the temperature fluctuation in a water body is relatively small, its seasonal variation can markedly influence submerged macrophytes, especially under global climate warming scenarios. Previous studies have indicated that the lethal water temperatures of submerged macrophytes are generally less than 3 • C or higher than 45 • C [75,76]. In the temperature range of 10-20 • C, the seed germination rates of V. natans increase with temperature, but higher temperatures (e.g., 28 • C) may decrease the rates and speed up the germination [77].…”
Section: Temperaturementioning
confidence: 99%
“…Although the temperature fluctuation in a water body is relatively small, its seasonal variation can markedly influence submerged macrophytes, especially under global climate warming scenarios. Previous studies have indicated that the lethal water temperatures of submerged macrophytes are generally less than 3 • C or higher than 45 • C [75,76]. In the temperature range of 10-20 • C, the seed germination rates of V. natans increase with temperature, but higher temperatures (e.g., 28 • C) may decrease the rates and speed up the germination [77].…”
Section: Temperaturementioning
confidence: 99%
“…It attained peaks of growth when the water temperature reached 28-29°C in the upper Paraná River (Sousa et al, 2010). Lethal water temperatures of SAMs are ones generally less than 3°C or higher than 45°C in their natural habitats (Best and Boyd, 2003;Christy and Sharitz, 1980). However, in a laboratory setting, H. verticillata has shown survival of some assessable physiological activities at 44°C, a finding that indicates its resilience towards thermophilicity (Chen, 1989; Van et al, 1976;Zhu et al, 2017).…”
Section: Temperaturementioning
confidence: 99%